2017
DOI: 10.18632/oncotarget.20359
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG15 inhibits P15 and KLF2 expression to promote pancreatic cancer proliferation through EZH2-mediated H3K27me3

Abstract: Long non-coding RNA (lncRNA) is emerging as an critical regulator in multiple cancers, including pancreatic cancer (PC). Recently, lncRNA SNHG15 was found to be up-regulated in gastric cancer and hepatocellular carcinoma, exerting oncogenic effects. Nevertheless, the biological function and regulatory mechanism of SNHG15 remain unclear in pancreatic cancer (PC). In this study, we reported that SNHG15 expression was also upregulated in PC tissues, and its overexpression was remarkably associated with tumor size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 68 publications
3
105
0
Order By: Relevance
“…A large quantity of evidence has revealed that lncRNAs could silence the expression of downstream target genes through binding to RNA‐binding proteins. For instance, Ma et al reported that a novel lncRNA, SNHG15, was capable of recruiting EZH2 to P15 and Kruppel‐like factor 2 (KLF2) promoter regions and repressed transcriptions of P15 and KLF2 through H3K27me3 modification to promote pancreatic cancer (PC) cell proliferation and inhibited apoptosis . Furthermore, Zhou et al showed that lncRNA PVT1 may promote thyroid cancer cell proliferation and cell cycle by regulating thyroid‐stimulating hormone receptor (TSHR) expression through binding to EZH2 .…”
Section: Discussionsupporting
confidence: 92%
“…A large quantity of evidence has revealed that lncRNAs could silence the expression of downstream target genes through binding to RNA‐binding proteins. For instance, Ma et al reported that a novel lncRNA, SNHG15, was capable of recruiting EZH2 to P15 and Kruppel‐like factor 2 (KLF2) promoter regions and repressed transcriptions of P15 and KLF2 through H3K27me3 modification to promote pancreatic cancer (PC) cell proliferation and inhibited apoptosis . Furthermore, Zhou et al showed that lncRNA PVT1 may promote thyroid cancer cell proliferation and cell cycle by regulating thyroid‐stimulating hormone receptor (TSHR) expression through binding to EZH2 .…”
Section: Discussionsupporting
confidence: 92%
“…To investigate the prognostic value of SNHG15 expression in patient with thyroid cancer, we evaluated the relationship of SNHG15 expression with disease-free survival and overall survival in thyroid cancer patient's cohort from TCGA database, and found low-expression of SNHG15 was associated with short disease-free survival, but there was no correlation between SNHG15 expression and overall survival in patients with thyroid cancer. 18 Up to now, present studies suggested that SNHG15 acted as an oncogenic lncRNA to regulate tumor cell proliferation, cell-cycle, apoptosis, and migration. 12,13 In addition, Kong and Qiu indicated patients with breast cancer having SNHG15 overexpression exhibited unfavorable overall survival.…”
Section: Discussionmentioning
confidence: 82%
“…14 Moreover, SNHG15 overexpression also has been showed to act as poor prognostic factor in digestive system tumors including hepatocellular carcinoma, 15 gastric cancer, 16 colon cancer, 17 and pancreatic cancer. 18 Due to low-expression of SNHG15 in thyroid cancer cell lines, we conducted gain-of-function study to explore the effect of SNHG15 in thyroid cancer cell, and found SNHG15 overexpression suppressed cell proliferation, migration, and invasion in thyroid cancer, which was inconsistent with the effect of SNHG15 in other cancers. In lung cancer cell, knocking down SNHG15 markedly suppressed cell proliferation, migration, and invasion, and induced cell apoptosis and cell-cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA PVT1 could bind with EZH2 to epigenetically silence LATS2 expression, thus contributing to non-small cell lung cancer (NSCLC) proliferation [57]. In our previous study, we also reported that lncRNA SNHG15 could interact with EZH2 in pancreatic cancer [58]. Here, we performed RIP experiments, and found that endogenous SH3PXD2A-AS1 exhibited significant enrichment in the anti-EZH2 RIP fraction in SW480 and DLD-1 cells.…”
Section: Discussionmentioning
confidence: 91%